The Use of Social Media by Student Affairs Practitioners - Rhonda Leece; Edward Campbell (JANZSSA)
Many student affairs professionals in the higher education sector consider the internet, social media, and other emerging technologies as peripheral to the real business of supporting students. There are however, many early adopters of this form of media driven engagement within the higher education sector. The 2011 Summer Edition of The Journal of Technology in Student Affairs (http://studentaffairs.com/ejournal/Summer_2011/) presents three articles which each offer an insight into the use of social media as a tool through which to engage, support and connect students and institutions. These articles represent the formative nature of online engagement and provide both encouragement and caution to the student affairs practitioners in higher education.